KINEMATIC ANALYSIS OF THE LAST STEP AND RELEASE STAGE IN MEN'S JAVELIN THROW (ResearchJet Journal of Analysis and Inventions, 2022)
The purpose of this study was to investigate the two-dimensional kinematic variables about the last step and release phase of the throwing technique of men's javelin throwers. For movement analysis, data were collected on 6 Iraqi javelin throwing athletes at the Iraq Championships in 2019. Recorded full-body video of athletes and javelin throwers during competition with a camera. High Speed (Casio Exilim EX-F1) set to 300 fps. The camera was positioned to the right and perpendicular to the runway to record the sagittal plane video. 2D coordinates were collected using (SkillSpector V1.3.2) software. The time, distance, speed, and angle around the last step and launch stage were analyzed, and the following was achieved; In order to throw the javelin effectively, subjects seem to spend more time on approach in the landing phase, and shorter delivery time in the release phase. On launch, it appears that the other items except player A1 are throwing in a state below their height. This result showed a slowdown in the speed of the project. To increase the projection velocity of the upper limb, joint in the launch event, it appears to extend the angle of the shoulder rather than increase the extension of the elbow joint. The body center of gravity angle body showed an almost incremental increase on the vertical axis in the firing event. But the anterior inclination angle of the trunk showed a small angle compared to the increase of the body by the body center of gravity angle. Therefore, in order to effectively transfer the momentum of the whole body in the javelin, the forward and backward inclination angle of the torso appears to rapidly transmit the angle displacement in the arc position or crescent state during the delivery motion of the launching stage. Therefore, Iraqi javelin throwers must practice the proper height, angle, and speed of the spear while firing. In order to achieve the effect of increasing the javelin throw distance further in the competition.